Clinical Trial of the Outpatient Management of Pyelonephritis in Pregnancy - Allyson M. Brooks; Thomas J. Garite (Hindawi Limited, 1995)
Objective: This study was designed to determine whether outpatient treatment of pyelonephritis in pregnancy can reduce costs without compromising safety or efficacy.